Estimativa para índice de hipersuperfícies mínimas fechadas na esfera - Sampaio, Paulo Ricardo Pinheiro (2009)
The objetive of this dissertation is to study the index of closed orientable non-totally geodesic minimal hypersurface Σn of the Euclidian unit sphere Sn+1 whose second fundamental form has squared norm bounded from below by n. In this case we shall show that the index of stability, denoted by IndΣn, is great than or equal to n + 3, with equality occurring at only Clifford tori Sk (√ k/n) X Sn-k (√n-k/n). Moreover, we shall prove also that, up to Clifford tori, we have the following, gap: IndΣn ≥ 2n + 5. This work is based in the article of Barros, A. and Sousa P., entiled "Estimate for index of closed minimal hypersurfaces in spheres" published in the Kodai Mathematical Journal at the year of 2009.